POTENSI EDAMAME SEBAGAI PENGGANTI KUNING TELUR DALAM PEMBUATAN DONAT MENGANDUNG KENTANG - Erni Sofia Murtini; Destiana Adinda Putri (Jurnal Teknologi dan Industri Pangan, 2017)
Addition of potato in doughnut will decrease the loaf volume, thus it requires the addition of egg yolk egg as emulsifiers to improve the loaf volume of the doughnut. Egg yolk is known to contain high cholesterol, therefore in this study edamame (Glycine max L. Merill) slurry is used as an egg yolk replacer. Five different proportions of edamame slurry were added to doughnut dough and their influence on the specific volume, porosity, water content, oil absorption, texture of hardness, cohesiveness and springiness were observed. The optimum variable was determined based on highest loaf volume using Response Surface Method (RSM). Factor used for the RSM was the slurry proportion to achieve 7 levels which were then verified. The optimum treatment was the addition of 18.14% of edamame slurry with resulted in 117.53% of loaf volume, 2.92 N of hardness level, 0.83 of cohesiveness level, 4.45 of springiness level, 30.66% of water content, 7.68% of protein, 17.87% of fat, 8.04% of crude fiber, 0.74% of ashes, 43.06% of carbohydrate, and 16.55% of total sugar.